2023
DOI: 10.3390/s23104984
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic, Flow-Through, Liquid Reagent Fluorescence Sensor Applied to Oxygen Concentration Measurement

Dominik Gril,
Denis Donlagic

Abstract: A concept of a microfluidic fluorescent chemical sensing system is presented and demonstrated as a sensor for measurement of dissolved oxygen in water. The system utilizes on-line mixing of a fluorescent reagent with the analyzed sample, while it measures the fluorescence decay time of the mixture. The system is built entirely out of silica capillaries and optical fibers, and allows for very low consumption of the reagent (of the order of mL/month) and the analyzed sample (of the order of L/month). The propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…They demonstrated the device application using ibuprofen and generated a detection limit of 10 −8 M. 216 Gril et al presented a fluorescence-based sensor for detecting dissolved oxygen in water. The system is composed of silica capillaries and optical fibers, and upon testing, revealed an accuracy of 0.025 mg L −1 with a response time of less than 60 s. 217 Finally, Charles et al demonstrated a bifurcated 128-microchannel device for environmental monitoring of explosives. The device, constructed of PMMA, used fluorescence-based displacement immunoassay for explosive determination.…”
Section: Watermentioning
confidence: 99%
“…They demonstrated the device application using ibuprofen and generated a detection limit of 10 −8 M. 216 Gril et al presented a fluorescence-based sensor for detecting dissolved oxygen in water. The system is composed of silica capillaries and optical fibers, and upon testing, revealed an accuracy of 0.025 mg L −1 with a response time of less than 60 s. 217 Finally, Charles et al demonstrated a bifurcated 128-microchannel device for environmental monitoring of explosives. The device, constructed of PMMA, used fluorescence-based displacement immunoassay for explosive determination.…”
Section: Watermentioning
confidence: 99%